Strategies for developing students' empathy and awareness for the needs of people with disabilities: Contributions to design education - Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika; Ferrari, Ana Lya Moya [UNESP]; Rodrigues, Ana Claudia Tavares (IOS Press, 2018)
The design of products for people with disabilities requires the understanding of a wide range of factors related to users' health, functional abilities, needs, expectations and preferences. Such multifactorial perspective is often perceived as beyond the reach by the students of both graphic and product design, as it comprises knowledge from different areas such are not usually part of design curriculum as health, rehabilitation, computer science and biomedical engineering. Here, we report on strategies for developing design students’ empathy and awareness for the needs and expectations of people with disabilities. By means of a combination of theoretical and practical approaches, a course on Inclusive Design was developed as part of the regular curriculum of the Bachelor Programme in Design at Sao Paulo State University (UNESP, Bauru campus, Brazil), with the collaborative participation of members of SORRI BAURU Rehabilitation Center. The final projects developed by the students were based on the demands presented by SORRI BAURU’s rehabilitation team, and results reveal that the theoretical-practical approach based on interdisciplinarity was shown to provide the design students a learning experience that, ultimately, supports the quality decision-making in the design process. This paper describes the pedagogical approach, theoretical contents and practical activities developed during the Inclusive Design course. The challenges, benefits, results, and contributions of this experience from the perspective of the design education are also discussed.
Keywords: Assistive Technologies; Design Education; Inclusive Design; Interdisciplinarity